2008
DOI: 10.1007/s10826-008-9226-x
|View full text |Cite
|
Sign up to set email alerts
|

Girls’ Disruptive Behavior and its Relationship to Family Functioning: A Review

Abstract: Although a number of reviews of gender differences in disruptive behavior and parental socialization exist, we extend this literature by addressing the question of differential development among girls and by placing both disruptive behavior and parenting behavior in a developmental framework. Clarifying the heterogeneity of development in girls is important for developing and optimizing gender-specific prevention and treatment programs. In the current review, we describe the unique aspects of the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 138 publications
(190 reference statements)
2
47
0
1
Order By: Relevance
“…Research and theorizing on gendered socialization suggests that the influence of family factors on antisocial behavior should be stronger for girls than boys (Chesney-Lind 1997;Kroneman et al 2009;Kruttschnitt and Giordano 2009). In other words, even if boys and girls experience similar levels of parental supervision or support, the protective benefits of these experiences should reduce delinquency more for girls than boys because they have been socialized into more passive gender roles, which emphasize relational bonding and a stronger adherence to parental norms (Fagan et al 2011).…”
Section: Gender Family Functioning and Immigrant Assimilationmentioning
confidence: 99%
“…Research and theorizing on gendered socialization suggests that the influence of family factors on antisocial behavior should be stronger for girls than boys (Chesney-Lind 1997;Kroneman et al 2009;Kruttschnitt and Giordano 2009). In other words, even if boys and girls experience similar levels of parental supervision or support, the protective benefits of these experiences should reduce delinquency more for girls than boys because they have been socialized into more passive gender roles, which emphasize relational bonding and a stronger adherence to parental norms (Fagan et al 2011).…”
Section: Gender Family Functioning and Immigrant Assimilationmentioning
confidence: 99%
“…Numbers in superscript indicate statistically significant differences between groups based on pairwise comparisons studies have found referred females to display more risk factors then referred males (e.g. Chamberlain and Reid 1994;Connor et al 2004;Fasulo et al 2002;Handwerk et al 2006;Kroneman et al 2009;McCabe et al 2002;Weis et al 2005). Another explanation may be that female's symptoms may simply tend to be more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there may be phenotypical differences in the disruptive behavior displayed by female youth. Males have an increased likelihood for physical aggression, while females are more likely to exhibit conflicts with authority figures (Lahey et al 2000;Maughan et al 2000) and display relational aggression (e.g., ostracizing and rumor spreading; Kroneman et al 2009). Thus, while many residential treatment programs were originally designed to serve male youth, the increase in disruptive behavior exhibited by female adolescents has led to an influx of females being referred to residential treatment (Weis et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deze gelijke mate van verandering in overreactiviteit suggereert dat de verschillende beginniveaus van overreactiviteit bij jongens en meisjes hun oorsprong hebben in de vroege(re) kindertijd. De sterkere oriëntatie van meisjes dan jongens op sociale relaties (Kroneman, Loeber, Hipwell, & Koot, 2009) is een mogelijke verklaring voor de bevinding dat overreactiviteit seksespecifiek is: omdat meisjes meer meegaand zijn dan jongens, zouden ouders minder geneigd kunnen zijn overreactiviteit te vertonen bij meisjes. Voor warmte vonden we wel een seksespecifieke ontwikkeling.…”
Section: Discussieunclassified